Evaluation of Potential Native Phosphate Solubilizing Bacteria for the Agriculture Practice of okra (Abelmoschus Esculentus) with the Target to Replace Chemical Fertilizer - in a Field Study - Sajeesh, P; Paulraj, P; Jaamuna, V; Jayakumar, N; P Sajna, K; Chandramohan, M; Ketharin, T; T Mohamed Javad, P (International Journal of Engineering and Technology, 2019)
Phosphorus (P) is a major growth limiting nutrient. Phosphate Solubilizing Bacteria (PSB) plays an important role in the development of agricultural industry. In this study, the native PSB were isolated from the okra plant root by using Pikovskayaâ€™s medium and potential strains were selected based on the phosphate solubilization efficiency. The potential strains in presence of Rock Phosphate (RP), Tea dust, Eggshells and Bone waste of animal (TEB) were studied as an alternative fertilizer instead of chemical fertilizer. The PSB consortia strains were prepared and inoculated to the plant root. Different growth parameters were studied to determine the effectiveness of strains. In all cases the difference was significant with p<0.05. A decreasing trend of results were recorded among the tested parameters from plants in PSB with RP, PSB with TEB, and PSB with TSP and followed by PSB without fertilizer. The highest results were recorded among plants in PSB with RP for mean shoot length (64cm), mean weight of fruits (29gm), mean length of fruits (23cm), mean number of leaves (13Nos) and chlorophyll content (5.1mg/g). Hence, the present study showed that the application of PSB with the cheap source of nutrients has shown the capability of providing similar or enhanced results based on the various characters expressed by the plant and thus reduce the reliance on synthetic chemical fertilizers.Â